Local Planning and Economic Restructuring: A Synthetic Interpretation of Urban Redevelopment - Jason Hackworth (Journal of Planning Education and Research 18 199 pp.293-306., 1999)
This paper presents an analysis of commercial land redevelopment in the Phoenix Metropolitan area during the late 1980s and early 1990s. Using four specific cases, I show how local landscape change is connected to the broader forces of urban restructuring. In addition, I discuss important differences between the city-building process in a central core and a suburban process within this structural context. The local deviations from the structural context are explained vis-a-vis the Phoenix regional economy, conservative political culture, and relative youth on the American urban frontier.